Wedding Organizer Order Management - Desi Maya Kristin; Yuliana Lisanti (ComTech: Computer, Mathematics and Engineering Applications, 2014)
This information system is used as a solution that can help to meet the requirements of the couples. The research methods are data collection, analysis and design. Data collection method implemented by surveys including interviews with 58 clients, 15 vendors, and 12 WO (Wedding Organizer) and by literature study that includes books and journal related. Object oriented is used as the method for system analysis and design. The result is a web based information system that connects vendors and clients in one online place. The web based application can be used to book the reception hall, catering food for guests, entertainments, bridal, car loan, prewed and receptions photos. The benefits of the web based applications are user can costumize or choose the packages, check the price information and get reports related to Wedding Organizer Order Management business process. The results of the qualitative interviews to 58 clients who already used the applications is the client get shorter time compare to clients who manage their own wedding reception.